(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Lake Onego, as one of the largest water bodies in a humid zone, is the recipient of terrestrial carbon and plays an important role in the global balance of this element. Due to heterotrophic metabolism in the Lake Onego ecosystem, substantial emissions of carbon dioxide from this lake into the atmosphere can be assumed. However, the extent of this phenomenon is still poorly known. As a climate change has led to an increase in water and organic matter flow into the northern water bodies, the carbon balance study of aquatic ecosystems is of particular relevance. The elements of the water balance for the Lake Onego catchment area in the current climate conditions are assessed. Based on satellite images the model of Lake Onego watershed terrestrial ecosystems is used to simulate the flow of organic matter into the lake with different types of vegetation and topography consideration. The assessment of the benthic communities habitat is carried out taking into account the accumulation of organic matter in various parts of Lake Onego.